2021
DOI: 10.2174/1871530321666210421123759
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Thalassemic Patients: The Role of Endocrine Defect Compensation

Abstract: Background: The improvement of beta thalassaemia treatments has led to an increase in life expectancy. This implies the emergence of new comorbidities. Amongst others, endocrine glands are extremely sensitive to iron overload. Objective: We aimed to understand the burden of the endocrine conditions on the patient’s quality of life (QOL). Results: Hypogonadism may present with lack or delay of pubertal development, sexual dysfunctions and impaired fertility, which impact QOL in both sexes. Early recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Regarding previous study of disease-related complications in adolescent and adult Thai population with TDT and NTDT, [6][7][8] Thalassemia-related complications profoundly impact the medical and socioeconomic burden, including quality of life 30,31 for the patients with thalassemia, hence the importance of early clinical screening and management in particular complications of the respective age group should be emphasized. We found that the most common complications as infections were correlated with splenectomy and elevated pre-transfusion Hb.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding previous study of disease-related complications in adolescent and adult Thai population with TDT and NTDT, [6][7][8] Thalassemia-related complications profoundly impact the medical and socioeconomic burden, including quality of life 30,31 for the patients with thalassemia, hence the importance of early clinical screening and management in particular complications of the respective age group should be emphasized. We found that the most common complications as infections were correlated with splenectomy and elevated pre-transfusion Hb.…”
Section: Discussionmentioning
confidence: 99%
“…TED massively impacts the medical and social burden, including the quality of life [ 45 ]. Specific therapy for BTH might improve endocrine involvement by correcting underling mechanisms such as IO; however, not all the studies agree on specific BTH treatment-ED association.…”
Section: Thalassemic Endocrine Diseasementioning
confidence: 99%
“…Since the patients with intermediate BTH have different clinical presentations, EDs vary, and a subgroup of subjects was similar to patients with major BTH with regards to the profile of EDs [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Overall, short stature affects both children and adults; GH/IG...…”
Section: Thalassemic Endocrine Diseasementioning
confidence: 99%